PREFERENSI PENGELOLA BADAN USAHA MILIK DESA (BUMDes) TERHADAP PENERAPAN PRODUK KEUANGAN SYARIAH (STUDI PADA BUMDes DI KECAMATAN TAMBANG) - Hertina Hertina; Haniah Lubis; Madona Khairunisa; Nurnasrina Nurnasrina (Jurnal Ilmiah Ekonomi Dan Bisnis, 2022)
Tambang District with a Muslim majority population, it is certain that the people of Tambang District are easier to accept Islamic values ​​and principles in carrying out BUMDes management activities that they manage. The purpose of this study is to find out the preferences of Village Owned Enterprises (BUMDes) managers towards the application of Islamic financial products, as well as the supporting and inhibiting factors for the application of Islamic financial products in the management of BUMDes in Tambang District. This research is field research, and the data analysis in this study uses descriptive qualitative analysis. The results showed that the preference of BUMDes managers towards the application of Islamic financial products in Tambang District viewed from the social, individual and sociological aspects was very good and strong. Supporting factors for the implementation of Islamic financial products are government support and managers' perceptions. Meanwhile, the inhibiting factor is technical problems after the system changes from conventional and sharia systems. Keyword: preference,Village Owned Enterprises (BUMDes), Islamic financial products